Emotional Intelligence as a Key Factor for the Success of Microentrepreneurs in Ecuador - Pérez-Salazar, Jazmin Alexandra; Fernández-Ronquillo, Mario Alfredo; Espinoza-Solís, Eduardo Javier; Echeverría-Vásquez, Huber Gregorio (Journal of Posthumanism, 2025)
This study analyzes the impact of emotional intelligence (EI) on the productive performance of micro-entrepreneurs in Zone 5 of Ecuador, which includes the provinces of Guayas, Santa Elena, and Los Ríos. EI, defined as the ability to recognize, understand, and manage one’s own and others’ emotions, is crucial for business success, especially in contexts with limited resources and high uncertainty. Since microenterprises represent over 80% of employment in Ecuador, EI is essential for overcoming challenges such as limited access to financing, informality, and deficiencies in management skills. Using a quantitative approach, 200 micro-entrepreneurs from the commercial, industrial, and service sectors were surveyed, employing validated instruments such as the Bar-On Emotional Intelligence Inventory and the Mayer-Salovey-Caruso Emotional Intelligence Test. The results showed that EI significantly influences productive performance (r = 0.501), with empathy and social skills being the most influential dimensions. Micro-entrepreneurs in the service sector achieved higher EI and performance scores, while no significant gender differences were found, although women excelled in customer satisfaction. The study suggests implementing EI workshops, creating support networks, and promoting self-assessment tools to strengthen business management and ensure the sustainability of microenterprises in the region.